BAY 87‐2243, a highly potent and selective inhibitor of hypoxia‐induced gene activation has antitumor activities by inhibition of mitochondrial complex I. (20th August 2013) - Ellinghaus, Peter; Heisler, Iring; Unterschemmann, Kerstin; Haerter, Michael; Beck, Hartmut; Greschat, Susanne; Ehrmann, Alexander; Summer, Holger; Flamme, Ingo; Oehme, Felix; Thierauch, Karlheinz; Michels, Martin; et al.
Abstract: The activation of the transcription factor hypoxia‐inducible factor‐1 (HIF‐1) plays an essential role in tumor development, tumor progression, and resistance to chemo‐ and radiotherapy. In order to identify compounds targeting the HIF pathway, a small molecule library was screened using a luciferase‐driven HIF‐1 reporter cell line under hypoxia. The high‐throughput screening led to the identification of a class of aminoalkyl‐substituted compounds that inhibited hypoxia‐induced HIF‐1 target gene expression in human lung cancer cell lines at low nanomolar concentrations. Lead structure BAY 87‐2243 was found to inhibit HIF‐1α and HIF‐2α protein accumulation under hypoxic conditions in non‐small cell lung cancer (NSCLC) cell line H460 but had no effect on HIF‐1α protein levels induced by the hypoxia mimetics desferrioxamine or cobalt chloride. BAY 87‐2243 had no effect on HIF target gene expression levels in RCC4 cells lacking Von Hippel–Lindau (VHL) activity nor did the compound affect the activity of HIF prolyl hydroxylase‐2. Antitumor activity of BAY 87‐2243, suppression of HIF‐1α protein levels, and reduction of HIF‐1 target gene expression in vivo were demonstrated in a H460 xenograft model. BAY 87‐2243 did not inhibit cell proliferation under standard conditions. However under glucose depletion, a condition favoring mitochondrial ATP generation as energy source, BAY 87‐2243 inhibited cell proliferation in the nanomolar range. Further experiments revealed that BAY 87‐2243 inhibits mitochondrial complex I activity but has no effect on complex III activity. Interference with mitochondrial function to reduce hypoxia‐induced HIF‐1 activity in tumors might be an interesting therapeutic approach to overcome chemo‐ and radiotherapy‐resistance of hypoxic tumors. Abstract : This study explores for the first time the effects of the novel, highly potent and selective hypoxia‐inducible factor (HIF) pathway inhibitor BAY 87‐2243 on HIF target gene expression levels in vitro and in vivo. BAY 87‐2243 exerts its effect on HIF‐1 pathway by inhibition of mitochondrial complex I and demonstrates anti‐tumor efficacy in vivo.